SOCIAL POLICY CHANGES IN THE THREE BALTIC STATES OVER THE LAST DECADE (2000–2012) - Aidukaitė, Jolanta (Ekonomika, 2013)
Abstract. This paper deals with changes in social policy (social security and health care) in the three Baltic states over the last decade. It seeks to elucidate the emerging differences among the three Baltic states in their social policy arrangements. The study employs inductive methods for the analysis of social security institutions, pursuing a comparative institutional analysis by means of macro level descriptive statistics. The paper demonstrates that in the period 2008–2012, the differences among the three countries in social policy arrangements have exacerbated. Estonia has handled the global financial crisis much better and managed to keep more solidarity and universalism in so cial policy as well as higher benefit levels as compared with Latvia and Lithuania. Key words: social security, health care, Baltic states, welfare state, differences